Exploring genetic and non‐genetic risk factors for delayed graft function, acute and subclinical rejection in renal transplant recipients. (10th May 2016) - Moes, Dirk Jan A. R.; Press, Rogier R.; Ackaert, Oliver; Ploeger, Bart A.; Bemelman, Frederike J.; Diack, Cheikh; Wessels, Judith A. M.; van der Straaten, Tahar; Danhof, Meindert; Sanders, Jan‐Stephan F.; Homan van der Heide, Jaap J.; Guchelaar, Henk Jan; et al.
Abstract : Aims: This study aimed at identifying pharmacological factors such as pharmacogenetics and drug exposure as new predictive biomarkers for delayed graft function (DGF), acute rejection (AR) and/or subclinical rejection (SCR). Methods: Adult renal transplant recipients ( n  = 361) on cyclosporine‐based immunosuppression were followed for the first 6 months after transplantation. The incidence of DGF and AR were documented as well as the prevalence of SCR at 6 months in surveillance biopsies. Demographic, transplant‐related factors, pharmacological and pharmacogenetic factors ( ABCB1, CYP3A5, CYP3A4, CYP2C8, NR1I2, PPP3CA and PPP3CB ) were analysed in a combined approach in relation to the occurrence of DGF, AR and prevalence of SCR at month 6 using a proportional odds model and time to event model. Results: Fourteen per cent of the patients experienced at least one clinical rejection episode and only DGF showed a significant effect on the time to AR. The incidence of DGF correlated with a deceased donor kidney transplant (27% vs. 0.6% of living donors). Pharmacogenetic factors were not associated with risk for DGF, AR or SCR. A deceased donor kidney and acute rejection history were the most important determinants for SCR, resulting in a 52% risk of SCR at 6 months ( vs. 11% average). In a sub‐analysis of the patients with AR, those treated with rejection treatment including ATG, significantly less frequent SCR was found in the 6‐month biopsy (13% vs. 50%). Conclusions: Transplant‐related factors remain the most important determinants of DGF, AR and SCR. Furthermore, rejection treatment with depleting antibodies effectively prevented SCR in 6‐month surveillance biopsies.